2018
DOI: 10.1016/j.btre.2018.e00269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lipid concentration on thermophilic anaerobic co-digestion of food waste and grease waste in a siphon-driven self-agitated anaerobic reactor

Abstract: HighlightsAnaerobic co-digestion of grease trap waste and food waste is feasible.Higher methane yield was achieved in the co-digestion compared with mono-digestion.Biogas production decreased due to lipid accumulation at high lipid concentrations.Temperature and mixing frequency play a key role in the lipid distribution.Lipid concentration under 40% is recommended in the co-digestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Anaerobic digestion is one of the most efficient treatment approaches for different kinds of waste biomass such as sewage sludge, livestock manure, food waste and agricultural waste [ 3 , 4 ]. Nowadays, the anaerobic digestion of energy crops has been widely applied in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic digestion is one of the most efficient treatment approaches for different kinds of waste biomass such as sewage sludge, livestock manure, food waste and agricultural waste [ 3 , 4 ]. Nowadays, the anaerobic digestion of energy crops has been widely applied in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, it can be seen that C/N ratio of FW and CD did not fall in the optimum range, which were reported (Section 2.1) to be 60 (FW) and 8 (CD). Furthermore, FW contains lipids; therefore, during the digestion of lipids in FW, long-chain fatty acids (LCFAs) are produced [62]. The presence of LCFAs caused inhibition in the AD system and obstructed the production of biogas [63].…”
Section: Biogas Production At Different Olrsmentioning
confidence: 99%
“…According to literature reports, improved process performance was observed with the addition of GTW to different co-substrates, such as sewage sludge [11], animal manure [12], and FW [13]. Compared with other main-substrates, anaerobic co-digestion of FW with GTW provides an economic option for on-site waste treatment in urban areas because of the close proximity of those two organic wastes [14]. In fact, a tall building in a Japanese city center has recently installed a small biogas generator system for the anaerobic co-digestion of FW with GTW [15].…”
Section: Introductionmentioning
confidence: 99%
“…Alves et al [19] reported a novel inverted anaerobic sludge blanket reactor (IASB) to effectively enhance methane production from LCFA-containing wastewater in AD. In our previous study, a siphon-driven self-agitated anaerobic reactor (SDSAR) was developed for the anaerobic co-digestion of FW and GTW [14]. However, relatively low OLR (1 to 4 g VS/L/d) or long HRT (up to 80 d) are still the few feasible choices for actual FW treatment with traditional digesters to sustain stable AD process and avoid LCFA accumulation [7].…”
Section: Introductionmentioning
confidence: 99%